Novel antifungal agents in clinical trials [version 2; peer review: 2 approved] - Jacobs, Samantha E; Zagaliotis, Panagiotis; Walsh, Thomas J (F1000 research, 2022)
Invasive fungal diseases due to resistant yeasts and molds are an important and increasing public health threat, likely due to a growing population of immunosuppressed hosts, increases in antifungal resistance, and improvements in laboratory diagnostics.  The significant morbidity and mortality associated with these pathogens bespeaks the urgent need for novel safe and effective therapeutics.  This review highlights promising investigational antifungal agents in clinical phases of development: fosmanogepix, ibrexafungerp, rezafungin, encochleated amphotericin B, oteseconazole (VT-1161), VT-1598, PC945, and olorofim.  We discuss three first-in-class members of three novel antifungal classes, as well as new agents within existing antifungal classes with improved safety and tolerability profiles due to enhanced pharmacokinetic and pharmacodynamic properties.